ANALISIS GAYA KEPEMIMPINAN BERDASARKAN TEORI KISI-KISI MANAJERIAL PADA PT. BANK MANDIRI (PERSERO), TBK DAN HARIAN SUMUT POS MEDAN - Aprinawati Aprinawati; Dita Amanah; Fauzia Agustini (Universitas Medan Area, 2017)
Leadership is essentially the ability of a person to build, lead, direct and mobilize others to work together to achieve the goals set. To realize these goals, a leader needs to do a series of activities including directing the people involved in the organization he leads. In other words, the purpose is achieved or not an organization is dependent on leadership.Managerial grille developed by Robert Blake and Jane Mouton is one of leadership style theories regarding the orientation of the manager on duty (production) and employees (people), and a combination of the two. This grid illustrates how attentive leader on duty and in humans thus creating a style of management and leadership. There are five basic leadership styles which include style conqueror (impoverished style), leader style mid (middle-of-the-road style), the style of the team (team style), relaxed style (country club style) and work style (task style).Leadership style has many theories put forward by experts in the fieldhuman resources, but researchers interested in studying the style of leadership based on the theory of grille managerial Blake and Mouton at PT. Bank Mandiri (Persero), Tbk Medan and SUMUT Daily Post. The reason is because of the five leadership styles that can be applied by the company, as stated above. Researchers want to know what the leadership style that is applied to both the company's five leadership styles that are owned as well as to determine whether there are differences in leadership styles are applied from both companies are based on the theory of grille managerial.This research uses descriptive exploratory method by distributing questionnaires to employees to identify leadership styles and the differences in the two companies studied.Keywords : grille managerial, leadership, leadership style